Early Neolithic Settlement Patterns in the Polish Lowlands – A Case Study of Selected Micro-Regions in Eastern Kuyavia - Pyzel Joanna (De Gruyter, 2021)
The purpose of this paper is the presentation of the settlement of the first farming communities of the Linear Pottery culture in the Polish lowlands. A case study of three neighboring micro-regions excavated on a large scale in eastern Kuyavia was conducted, which offered the possibility of analyzing various levels of the settlement. Based on the results obtained a local model of the LBK occupation in Kuyavia could be reconstructed. I argue that despite some regional variability a very general common settlement pattern existed for the whole LBK consisting of an iconic longhouse as the basic unit, the presence of micro-regional clusters of more or less contemporary sites, and the preference for regions with optimal environmental conditions. However, a detailed comparison within and between separate sites in the study area revealed some degree of variability inside this supposedly homogeneous pattern which can indicate the existence of different social units among small regional communities and their changes over time.